Application Method of Potassium Humate on Growth And Yield of Green Onion (Allium Cepa L.) - Yousif, Kurdistan H. (Science Journal of University of Zakho, 2014)
The experiment was carried out during October 2011 at the vegetative research farm, Faculty of Agriculture and Forestry, University of Duhok on onion (Allium cepa L. )., bulbs were planted in November -2011 .RandomizeCompleteBlock design (R.C.B.D.) was used in this experiment. Each treatment was replicated three times with 10 plants per each. The factors included the following; two concentrations of Potassium humate (0 and 1.8 gm.L-1) and application methods (foliar and fertigation),.Results showed that Potassium humate caused significant increase in most of vegetative growth characteristics .The dual interaction treatments among the tested factors at both fertilization methods especially by fertigation at the high levels revealed significant increase in vegetative characters. and significant increase occurred in the yield characters (bulbs weight, yield of a square meter kg.m2).